C9ORF72 poly-PR induces TDP-43 nuclear condensation via NEAT1 and is modulated by HSP70 activity - Diksha Agnihotri; Chi-Chang Lee; Po-Chao Lu; Ruei-Yu He; Yung-An Huang; Hung-Chih Kuo; Joseph Jen-Tse Huang (Cell Reports)
Summary: The toxicity of C9ORF72-encoded polyproline-arginine (poly-PR) dipeptide is associated with its ability to disrupt the liquid-liquid phase separation of intrinsically disordered proteins participating in the formation of membraneless organelles, such as the nucleolus and paraspeckles. Amyotrophic lateral sclerosis (ALS)-related TAR DNA-binding protein 43 (TDP-43) also undergoes phase separation to form nuclear condensates (NCs) in response to stress. However, whether poly-PR alters the nuclear condensation of TDP-43 in ALS remains unclear. In this study, we find that the poly-PR dipeptide enhances the formation of TDP-43 NCs with decreased fluidity. While the non-coding RNA, nuclear-enriched abundant transcript 1 (NEAT1), is essential for the formation of TDP-43 NCs, heat shock protein 70 (HSP70) chaperone maintains their fluidity. Under prolonged poly-PR stress, HSP70 delocalizes from TDP-43 NCs, leading to the oligomerization of TDP-43 within these condensates. This phenomenon is accompanied with TDP-43 mislocalization and increasing cytotoxicity. Our study demonstrates the role of NEAT1 and HSP70 in the aberrant phase transition of TDP-43 NCs under poly-PR stress.